Coercive Measures in Psychiatry: A Review of Ethical Arguments - Chieze, Marie; Clavien, Christine; Kaiser, Stefan; Hurst, Samia (Frontiers in Psychiatry, 2021)
Introduction Coercion is frequent in clinical practice, particularly in psychiatry. Since it overrides some fundamental rights of patients (notably their liberty of movement and decision-making), adequate use of coercion requires legal and ethical justifications. In this article, we map out the ethical elements used in the literature to justify or reject the use of coercive measures limiting freedom of movement (seclusion, restraint, involuntary hospitalization) and highlight some important issues. Methods We conducted a narrative review of the literature by searching the PubMed, Embase, PsycINFO, Google Scholar and Cairn.info databases with the keywords “coercive/compulsory measures/care/treatment, coercion, seclusion, restraint, mental health, psychiatry, involuntary/compulsory hospitalization/admission, ethics, legitimacy.” We collected all ethically relevant elements used in the authors’ justifications for or against coercive measures limiting freedom of movement (e.g., values, rights, practical considerations, relevant feelings, expected attitudes, risks of side effects), and coded, and ordered them into categories. Results Some reasons provided in the literature are presented as justifying an absolute prohibition on coercion; they rely on the view that some fundamental rights, such as autonomy, are non-negotiable. Most ethically relevant elements, however, can be used in a balanced weighting of reasons to favor or reject coercive measures in certain circumstances. Professionals mostly agree that coercion is only legitimate in exceptional circumstances, when the infringement of some values (e.g., freedom of movement, short-term autonomy) is the only means to fulfill other, more important values and goals (e.g., patients’ safety, the long-term rebuilding of patients’ identity and autonomy). The results of evaluations vary according to which moral elements are prioritized over others. Moreover, we found numerous considerations (e.g., conditions, procedural values) for how to ensure that clinicians apply fair decision-making procedures related to coercion. Based on this analysis, we highlight vital topics that need further development. Conclusion Before using coercive measures limiting freedom of movement, clinicians should consider and weigh all ethically pertinent elements in the situation and actively search for alternatives that are more respectful of patients’ well-being and rights. Coercive measures decided upon after a transparent, carefully balanced evaluation process are more likely to be adequate, understood, and accepted by patients and caregivers.